2018
DOI: 10.1038/s41419-017-0240-z
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation between Hsp90 and mortalin/GRP75 in resistance to cell death induced by complement C5b-9

Abstract: Cancer cells are commonly more resistant to cell death activated by the membranolytic protein complex C5b-9. Several surface-expressed and intracellular proteins that protect cells from complement-dependent cytotoxicity (CDC) have been identified. In this study, we investigated the function of heat shock protein 90 (Hsp90), an essential and ubiquitously expressed chaperone, overexpressed in cancer cells, in C5b-9-induced cell death. As shown, inhibition of Hsp90 with geldanamycin or radicicol is enhancing sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…However, cancer cells adapt escape mechanisms for MAC. Hsp90 protected tumor cells from complement-dependent cytotoxicity by inhibiting, together with mortalin, C5b-9 assembly and/or stability at the plasma membrane 9 .…”
Section: Conventional Complement Activation Pathwaysmentioning
confidence: 99%
“…However, cancer cells adapt escape mechanisms for MAC. Hsp90 protected tumor cells from complement-dependent cytotoxicity by inhibiting, together with mortalin, C5b-9 assembly and/or stability at the plasma membrane 9 .…”
Section: Conventional Complement Activation Pathwaysmentioning
confidence: 99%
“…MAC blockage can also be triggered by the Heat shock protein 90 (Hsp90). This protein directly interacts with the C9 molecules, are sequestered, preventing the polymerization and formation of the MAC [71]. Table 2.…”
Section: Complement Biomarkers In Patients With Cancermentioning
confidence: 99%
“…As a molecular chaperone, the main function of HSP90 is to regulate the stability and activity of the client protein, which is pivotal for maintaining cell structure and function and inhibiting apoptosis 27,28 . Recent studies have shown that HSP90 binds to the chaperone-mortalin protein to attenuate complementmediated cell lysis 29 , while HSP90 inhibitors promote this process 14,15 . Therefore, HSP90 is an emerging therapeutic target in I/R injury and cardioprotection 12,13 .…”
Section: ■ Discussionmentioning
confidence: 99%